A Companhia de Jesus no Brasil durante o reinado de Filipe II: transformações e permanências - Oliveira, Pedro Hermes De (2017)
This research examines the beginning of the colonization of Brazil, especially about the evangelization carried out by the missionaries of Jesus Company, between 1549 and 1598. I will introduce the trajectory of religious people evangelization, in XVI century concentrating some information about the arrival of Ignatian people in Brazil with the evangelization between the natives and the changes in the Jesuit way of being, when the members of the Company in Brazil were then governed by the Spanish King Philip II. In order to contribute for the studies about the conquest in the New World, I will make a compilation of Philip II trajectory, focusing on aspects that led him to the dispute and conquest of the Portuguese throne. There are two important aspects to note here: the Jesuits were the only missionaries of the Catholic Church in Colonial Brazil until the beginning of the Iberian Union and Philip II had no sympathy for the Ignatian people in his kingdom. Although the Jesuits were chosen for the Ultramar Project that propagated the territorial expansion and defense of Spanish America, the missionaries prioritized efforts for the consolidation of the Colleges.